Hukum Perjanjian: Studi Penerapan Asas Konsensualisme sebagai Syarat Sahnya Perjanjian Bisnis Digital - Muhammad Arifaturahman; Kasmar Kasmar; Didik Irawansah (Jurnal Hukum Lex Generalis, 2026)
The regulation of business agreements in Indonesia is fundamentally rooted in the Civil Code (KUHPerdata), particularly Book III on Obligations, which embodies the principles of freedom of contract, consensualism and good faith. Despite its colonial origin, these provisions remain the primary foundation of modern business activities. Business agreements encompass not only contracts explicitly regulated by law, such as sale and lease, but also evolve into non-conventional forms responding to commercial needs, including franchises, joint ventures, leasing and electronic contracts. Such developments are reinforced by sectoral regulations on consumer protection, electronic transactions, limited liability companies and financial supervision, which contain both regulatory and mandatory norms to maintain balance between parties. Within this framework, the principle of consensualism occupies a central position as a requirement for contractual validity, whereby an agreement is formed solely through mutual consent, without specific formalities unless prescribed by law. This principle grants flexibility to business actors but remains constrained by good faith, propriety and protection of weaker parties. In the digital era, consent may also be expressed electronically, requiring a progressive interpretation that emphasizes substantive justice rather than mere formal agreement.